2013
DOI: 10.1590/s0102-311x2013000100011
|View full text |Cite
|
Sign up to set email alerts
|

Secular trends in the rate of low birth weight in Brazilian State Capitals in the period 1996 to 2010

Abstract: Malaria epidemics occur annually in various municipalities (counties)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 49 publications
0
18
0
2
Order By: Relevance
“…However, these findings differed from Ribeirão Preto, where the LBW rate increased from 7.2% in 1978/1979 to 10.6% in 1994 30 . Based on birth registry data, an increase in LBW rate was also observed in Brazil's state capitals as a whole 15 , but not in the country as a whole 31 . PTB rates were also stable in the two periods in the São Luís cohorts, at around 13%.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…However, these findings differed from Ribeirão Preto, where the LBW rate increased from 7.2% in 1978/1979 to 10.6% in 1994 30 . Based on birth registry data, an increase in LBW rate was also observed in Brazil's state capitals as a whole 15 , but not in the country as a whole 31 . PTB rates were also stable in the two periods in the São Luís cohorts, at around 13%.…”
Section: Discussionmentioning
confidence: 96%
“…The LBW rate increased from 8.5% in 1996 to 9.1% in Brazil's state capitals 15 . Temporal analysis in the Ribeirão Preto cohorts also showed an increase in the LBW rate from 7.2% in 1978/1979 to 10.6% in 1994 16 , but comparison of the 1982 and 2004 birth cohorts showed that LBW has not increased in Pelotas 14 .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Brazil is a country with high disparities in social, economic, and health conditions (Veloso et al, ). Further, the prevalence of overweight/obesity in children and adolescents has increased during the last decades (Instituo Brasileiro de Geografia e Estatística (IBGE), ; Veloso et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Brazil is a country with high disparities in social, economic, and health conditions (Veloso et al, ). Further, the prevalence of overweight/obesity in children and adolescents has increased during the last decades (Instituo Brasileiro de Geografia e Estatística (IBGE), ; Veloso et al, ). According to nationally representative surveys by the Brazilian National Statistics Agency in 1974–1975 and 2008–2009, overweight prevalence in children (aged 5–9 years) increased from 10.9% to 34.8% and from 8.6% to 32%, in boys and girls, respectively; while the prevalence of obesity increased from 2.9% to 16.6% in boys, and from 1.8% to 11.8% in girls (IBGE, ).…”
Section: Introductionmentioning
confidence: 99%